2012
DOI: 10.1098/rsbl.2012.0338
|View full text |Cite
|
Sign up to set email alerts
|

Hot or not? Thermal reactions to social contact

Abstract: Previous studies using thermal imaging have suggested that face and body temperature increase during periods of sexual arousal. Additionally, facial skin temperature changes are associated with other forms of emotional arousal, including fear and stress. This study investigated whether interpersonal social contact can elicit facial temperature changes. Study 1: infrared images were taken during a standardized interaction with a same-and opposite-sex experimenter using skin contact in a number of potentially hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
67
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 16 publications
2
67
1
Order By: Relevance
“…Thermo-imaging could capture how the individuals behaviorally react to social stress in a complex social interaction. Forth, in humans, sexual arousal causes the increase in nasal and perioral temperatures (Hahn et al, 2012;Merla & Romani, 2007), an opposite effect that we observed in this study. Sexual interest is one of the major behavioral drives in primates; yet its physiological and psychological underpinnings remain relatively unclear (Deaner, Khera, & Platt, 2005).…”
Section: Accepted Manuscriptcontrasting
confidence: 58%
See 1 more Smart Citation
“…Thermo-imaging could capture how the individuals behaviorally react to social stress in a complex social interaction. Forth, in humans, sexual arousal causes the increase in nasal and perioral temperatures (Hahn et al, 2012;Merla & Romani, 2007), an opposite effect that we observed in this study. Sexual interest is one of the major behavioral drives in primates; yet its physiological and psychological underpinnings remain relatively unclear (Deaner, Khera, & Platt, 2005).…”
Section: Accepted Manuscriptcontrasting
confidence: 58%
“…driving (Or & Duffy, 2007), numeric task (Kang, McGinley, McFadyen, & Babski-Reeves, 2006)] decreased the nasal (and perinasal) temperature. Sexual arousal, induced by intimate touch (Hahn, Whitehead, Albrecht, Lefevre, & Perrett, 2012), interpersonal proximity and eye contact , and viewing erotic movies (Merla & Romani, 2007), caused the opposite effect; the increase in nasal (and perioral) temperature due to the increased blood flow. In monkeys, presentation of potentially fearful or stressful stimuli, such as a threatening experimenter, videos of screaming and threatening monkeys, caused the decrease in nasal temperature (Kuraoka & Nakamura, 2011;Nakayama, Goto, Kuraoka, & Nakamura, 2005).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Unlike conventional methods of autonomic monitoring, fITI provides versatility. It enables recording of perspiration (Ebisch et al., ; Pavlidis et al., ), cutaneous and subcutaneous temperature variations (Merla, Di Donato, Rossini, & Romani, ; Hahn, Whitehead, Albrecht, Lefevre, & Perrett, ), blood flow (Puri, Olson, Pavlidis, Levine, & Starren, ), cardiac pulse (Garbey, Sun, Merla, & Pavlidis, ), as well as metabolic breathing patterns (Pavlidis et al., ). The reliability of this tool has been repeatedly proven with the use of simultaneous recordings grounding fITI on gold standard methods, such as electrocardiography (ECG), piezoelectric thorax stripe for breathing monitoring, nasal thermistors, skin conductance, or galvanic skin response (GSR).…”
Section: Autonomic Nature Of the Thermal Print For Psychophysiologicamentioning
confidence: 99%
“…To perform thermal imaging recordings, researchers have used camera models of different resolution. The majority of studies used a camera with a resolution of 256 × 256 (Merla & Romani, ) to 320 × 240 (Calvin & Duffy, ; Ebisch et al., ; Hahn et al., ; Ioannou et al., ; Kang, McGinley, McFadyen, & Babski‐Reeves, ; Kuraoka & Nakamura, ; Pavlidis, Eberhardt, & Levine, ; Pavlidis et al., , ; Puri et al., ; Shastri, Papadakis, Tsiamyrtzis, Bass, & Pavlidis, ; Vianna & Carrive, ; Zhu et al., ). Recordings, however, of higher image quality such as 640 × 480 (Gane et al., ; Manini et al., ) to 640 × 512 (Pavlidis et al., ; Shastri et al., ) were relatively more rare.…”
Section: Autonomic Nature Of the Thermal Print For Psychophysiologicamentioning
confidence: 99%
“…Similarly, Ijzerman and Semin (2009) found that participants seated in a warm room report feeling interpersonally closer to the experimenter than do those seated in a colder room. Conversely, experiencing social rejection makes people feel physically cold (IJzerman et al, 2012;Zhong & Leonardelli, 2008), experiencing social connection makes people feel physically warm (Hahn et al, 2012;Inagaki & Eisenberger, 2013), and thinking about a target's sociability traits increases estimates of room temperature (Szymkow et al, 2013).…”
mentioning
confidence: 99%